Judging Mohammed : juvenile delinquency, immigration, and exclusion at the Paris Palace of Justice - Terrio, Susan J. (Susan Jane), 1950- (Stanford University Press, 2009)
This groundbreaking study goes inside France's juvenile court system and follows young people, largely of foreign ancestry, from arrest to court trials, revealing an alarming shift in the nation's approach to its youth offenders.